Goals and Methods of Islamic Education: Majid Irsan Al-Kailani's Perspective - Sinaga, M. Yunus; Arsyad, Junaidi; Salminawati, Salminawati (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to: (1) Describe the biography of Majid Irsan Al-Kailani (2) Analyze the goals and methods of Islamic education from Majid Irsan Al-Kailani's perspective (3) Analyze the relevance of the development of goals and methods of Islamic education from Majid Irsan Al-Kailani's perspective with contemporary Islamic education. This type of research is qualitative research with library research method and figure study approach. The primary data source in this study is the book Ahdaf at-Tarbiyah al-Islamiyah Dirasah Muqaranah baina Ahdaf at-Tarbiyah al-Islamiyah wa al-Ahdaf at-Tarbawiyah al-Mu'asharah by Majid Irsan Al-Kailani and supported by Al-Kailani's works as well as books, journals, and scientific works related to the discussion in the study as secondary sources. The data analysis technique used is content analysis. The results of the study show that Majid Irsan Al-Kailani's thoughts on the goals and methods of Islamic education are very relevant to the present day. He formulated four main goals of education: the formation of good individuals (al-fard al-shalih), the Islamic family (al-usrah al-muslimah), the community of messengers (ummah al-risalah), and human brotherhood (al-ukhuwah al-insaniyah). All of these points culminate in the effort to produce complete human beings (al-insan al-kamil al-raqi) capable of realizing the vision of Islamic education by fostering a strong spiritual relationship between students and Allah SWT.